The Relationship Between Inventory Management Practices, Inventory Efficiency, and Supply Chain Information on the Business Performance of Indonesian MSMEs - Bryan Aubrey; Cindy Patricia; Glent Febrian; Gregorius Bagas Yogiswara; Yenny Suvena; Rudi Prasetyo Ardi (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the effect of Inventory Management Practices, Inventory Efficiency (Inventory Leanness), and Supply Chain Information on the Business Performance of MSMEs in Indonesia. This study employs a quantitative approach using explanatory research design. Data were collected through an online questionnaire distributed to 73 MSME owners across different regions in Indonesia using purposive sampling. The research instrument was developed based on established indicators for each variable and measured using a Likert scale. Data analysis was conducted using SPSS, including validity and reliability tests, multiple linear regression analysis, coefficient of determination (R²), F-test, and t-test to examine both simultaneous and partial effects among variables. The results indicate that Inventory Management Practices, Inventory Efficiency, and Supply Chain Information simultaneously have a significant effect on MSME Business Performance. The coefficient of determination (R²) value of 0.612 suggests that 61.2% of the variation in business performance can be explained by the three independent variables. However, partial testing reveals that Inventory Management Practices do not have a statistically significant effect on Business Performance (p = 0.076), despite showing a positive relationship. In contrast, Inventory Efficiency (p = 0.009) and Supply Chain Information (p = 0.001) have a significant and positive effect on Business Performance. These findings suggest that the ability of MSMEs to maintain lean and efficient inventory levels, along with fast, clear, and transparent supply chain information flow, contributes more substantially to business performance improvement than inventory management practices when implemented independently.